IMPROVE INDONESIAN LANGUAGE LEARNING OUTCOMES THROUGH THE PROBLEM BASED LEARNING MODEL IN FIFTH GRADES SDN 1 PALEMBANG - Jannah, Miftahul; Susanti, Rahmi; Nizayati, Fariyus (PROGRES PENDIDIKAN, 2025)
Study This aiming for increase results Study participant educates on the eyes Indonesian language lessons for Fifth grades with using the Problem Based Learning (PBL) model. Research This is study action classes held in two cycles. Subject study is student The Fifth grades consist of 28 people, 13 men and 15 women. Data collection techniques use observation, testing, and documentation. Research results show that the application of the PBL model can increase results studying Indonesian Language subjects. The average results obtained Study students in the eye Indonesian language lessons cycle I was 63.39 with category low, so that study to be continued to cycle II. In cycle II the average results Study student Indonesian language lessons are 79.64, with category high. Based on results research, can concluded that the Problem Based Learning model effective in increase results Study students in Indonesian language lessons in Fifth grades SDN 1 Palembang.